2004
DOI: 10.1046/j.0305-1846.2003.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in intracranial meningiomas: immunohistochemical and molecular study

Abstract: Much of the morbidity of intracranial meningiomas is related to the degree of tumour vascularity and the extent of peritumoural vasogenic oedema. Several studies have shown that vascular endothelial growth factor (VEGF) is up-regulated in meningiomas, although its relationship with tumour vasculature is still unclear. In order to better understand the angiogenic assessment of intracranial meningiomas, we analysed its vascular pattern, both as number and as morphologic configuration of microvessels. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 25 publications
3
72
2
Order By: Relevance
“…The elevated levels of VEGF seen in this study confirm earlier reports not only on benign meningiomas, but atypical and malignant ones as well (40). It has been suggested that the increased ratio of the pro-angiogenesis factor VEGF to the anti-angiogenic factor SEMASA (which is expressed in human meningiomas association with low microvessel density) is a negative predictor of recurrence in these neoplasms (41).…”
Section: Discussionsupporting
confidence: 80%
“…The elevated levels of VEGF seen in this study confirm earlier reports not only on benign meningiomas, but atypical and malignant ones as well (40). It has been suggested that the increased ratio of the pro-angiogenesis factor VEGF to the anti-angiogenic factor SEMASA (which is expressed in human meningiomas association with low microvessel density) is a negative predictor of recurrence in these neoplasms (41).…”
Section: Discussionsupporting
confidence: 80%
“…43 As our working group could demonstrate in a previous study including 17 dogs, its expression is a predictive factor for survival in dogs with intracranial meningiomas. 38 The current study confirmed in a large number of samples that VEGF is expressed in intracranial meningioma tissue from dogs, with positive labeling in 67/70 (96%) of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not reveal any association of VEGF and Ki-67 expression in intracranial meningioma in dogs, despite evidence that increased vascularization is associated with higher proliferation in human meningiomas. 43,44 It is interesting that even in the outlier that revealed an extraordinary high MIB-LI of 43.1, only 25-50% of cells stained positive for VEGF, and staining intensity was considered as mild. Upregulation of VEGF induced by hypoxia in the most central or necrotic components of the tumor 55 might have influenced results in our study as we did not control for the presence or absence of necrosis and no information was available on where within the tumor the sample was collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) and its receptors are reported to play a major role in angiogenesis, vascular permeability, and tumor recurrence in human meningiomas. 49,50 Both VEGF and its major receptor VEGFR-2 are upregulated in canine meningiomas. 6,8 Survival time for canine meningioma patients was inversely associated with VEGF expression in 1 series, 8 although all tumors were benign (Grade I).…”
mentioning
confidence: 99%